Influence of Instructional Leadership and Academic Supervision on The Quality of Learning - Ngatini Ngatini; Widya Kusumaningsih; Nurkolis Nurkolis; Milagros Racacho Baldemor (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study examines the impact of instructional leadership and academic supervision on learning quality in junior high schools within the Boja District. Method: Employing a quantitative approach with a correlational design, the research involved a total population of 140 teachers, from which 104 were selected as the sample. Data were collected through questionnaires and analyzed using descriptive statistics and hypothesis testing via simple and multiple linear regression. Result: The findings indicate that instructional leadership has a correlation of 0.820 and a significant influence of 77.2%, whereas academic supervision shows a correlation of 0.741 with a substantial impact of 64.9%. When examined together, these two factors enhance learning quality, with a coefficient of determination of 77.3%. These results highlight the crucial role of instructional leadership and academic supervision in improving educational outcomes. The study provides novel insights by reinforcing that strengthening these two aspects is a strategic measure for enhancing learning quality in junior high schools. This research contributes to the growing body of knowledge in educational leadership by emphasizing the importance of effective school management in fostering academic success. Novelty: The findings suggest that policymakers and school administrators should prioritize professional development programs that enhance leadership and supervision capacities, ensuring sustained improvements in teaching and learning processes.